Ekstrak Propolis Lokal Mempunyai Efek Sitotoksik dan Antiproliferatif Terhadap Sel HeLa - Hadiyah, Zauhani Kusnul; Widyarti, Sri; Widodo, Muhamad Aris (Fakultas Kedokteran Universitas Brawijaya, 2009)
ABSTRACTPropolis is resin with complex chemical composition that collected by honeybees from various plants. It hasbeen known that propolis has several biological properties, such as antimicrobial, anti-inflammatory,antioxidant and immunomodulatory activities. The aim of this study is to evaluate the propolis's cytotoxic andantiproliferative activity in vitro on hela cell line. These cells were incubated with different concentrations ofpropolis (5, 10, 25, 50, and 100 Âµg/ml) for different time periods (6, 24, dan 48 hours), and the number of viableand died cells were analyzed by trypan blue dye exclution and were counted using hemocytometer. Theresult of this study showed that the IC50 of local propolis against HeLa cell line is 27,725 Âµg/ml. It can beconcluded that local propolis extract exhibited a cytotoxic and antiproliferatif effect in vitro against HeLa cellline, in a dose- and time dependent.Key words: propolis, cytotoxic, antiproliferative, HeLa cell line